Are Investors Beyond Rationality? Uncovering Behavioral Finance in Stock Investment Decision Making: A Comprehensive Systematic Literature Review - Valsa Ayunda Tisya (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
Humans have complex natures, cannot be predicted or followed by theory. The emotional and cognitive aspects that play a role in financial decision making, especially stock investment, are very important to study. The contribution of this theory will be very useful in mitigating the risk of biased decision making. This article is based on the Systematic Literature Review (SLR) method. This systematic literature review examines a large number of studies on behavioral finance from 11 leading and reputable financial journals published between 2020 and 2024. Articles are collected through Harzing's Publish or Perish with Scopus and Google Scholar article data sources. This SLR research uses the keywords "behavioral finance", "stock" and "investment decision" and is selected using the PRISMA Systematic Literature Review Flow Chart, then analyzed using VOSviewers. The purpose of this article is to offer a comprehensive analysis of the existing literature by providing an overview of the publication pattern of articles over the past 5 years, a geographic map of contributing research, a list of top articles and journals, current topic trends and future research agendas that will greatly assist future researchers in exploring empirical research in the future.